Modeling of Xerostomia After Radiotherapy for Head and Neck Cancer: A Registry Study - Onjukka, Eva; Mercke, Claes; Björgvinsson, Einar; Embring, Anna; Berglund, Anders; Alexandersson von Döbeln, Gabriella; Friesland, Signe; Gagliardi, Giovanna; Lenneby Helleday, Clara; Sjödin, Helena; Lax, Ingmar (Frontiers in Oncology, 2020)
Data from a local quality registry are used to model the risk of late xerostomia after radiotherapy for head and neck cancer, based on dosimetric- and clinical variables. Strengths and weaknesses of using quality registry data are explored. Head and neck cancer patients treated with radiotherapy at Karolinska University hospital are entered into a quality registry at routine follow up, recording morbidity according to a modified RTOG/LENT-SOMA scale. Other recorded parameters are performance status, age, gender, tumor location, tumor stage, smoking status, chemotherapy and radiotherapy data, including prescribed dose and organ-at-risk dose. Most patients are entered at several time points, but at variable times after treatment. Xerostomia was modeled based on follow-up data from January 2014 to October 2018, resulting in 753 patients. Two endpoints were considered: maximum grade ≥2 (XERG≥2) or grade ≥3 (XERG≥3) late xerostomia. Univariate Cox regression was used to select variables for two multivariate models for each endpoint, one based on the mean dose to the total parotid volume (Dtot) and one based on the mean dose to the contralateral parotid (Dcontra). Cox regression allows the estimation of the risk of xerostomia at different time points; models were presented visually as nomograms estimating the risk at 9, 12 and 24 months respectively. The toxicity rates were 366/753 (49%) for XERG≥2 and 40/753 (5.3%) for XERG≥3. The multivariate models included several variables for XERG≥2, and dose, concomitant chemotherapy and age were included for XERG≥3. Induction chemotherapy and an increased number of fractions per week showed a protective effect regarding XERG≥2. However, since the causality of these relationships have limited support from previous studies, alternative models without these variables were also presented. The models based on the mean dose to the total parotid volume and the contralateral parotid alone were very similar. Late xerostomia after radiotherapy can be modelled with reasonable predictive power based on registry data; models are presented for different endpoints highly relevant in clinical practice. However, the risk of modeling indirect relationships, given the unavoidably heterogeneous and uncontrolled registry data, needs to be carefully considered in the interpretation of the results.